Hubungan Frekuensi KIE dan Riwayat Kesehatan Ibu Hamil dengan Kejadian BBLR - Andi Elis; Suriana Suriana; Andi Maryam; Sucianti Lestari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Low Birth Weight (LBW) remains a major public health problem contributing to neonatal morbidity and mortality. Maternal factors, including the frequency of receiving Communication, Information, and Education (CIE) and maternal health conditions during pregnancy, may influence the occurrence of LBW. This study aimed to determine the relationship between the frequency of CIE and maternal health history with the incidence of LBW in the working area of Wamena Public Health Center. A quantitative analytical study with a cross-sectional design was conducted involving 30 mothers who delivered LBW infants. Samples were selected using a total sampling technique. Data were collected through questionnaires, medical records, and health service documentation and analyzed using the Chi-Square test at a significance level of 0.05. The results showed that 50.0% of respondents had never received CIE during pregnancy, and most had a history of maternal health problems, particularly anemia (43.3%). Statistical analysis revealed significant relationships between CIE frequency and LBW incidence (p=0.025) and between maternal health history and LBW incidence (p=0.041). Strengthening maternal health education and early management of maternal health problems are essential strategies for reducing LBW incidence.